2003
DOI: 10.1111/j.1945-1474.2003.tb01025.x
|View full text |Cite
|
Sign up to set email alerts
|

Co-bedding Versus Traditional Bedding of Multiple-Gestation Infants in the NICU

Abstract: This study was part of a large departmental performance improvement initiative to implement and evaluate developmental and family-centered care as "best practice" in the neonatal intensive care unit (NICU). The goal was to evaluate the safety, effect on infant clinical and developmental outcomes, and maternal satisfaction of co-bedding of multiple-gestation infants compared to traditionally bedded infants/mothers. A secondary purpose was to evaluate co-bedding and American Academy of Pediatrics-recommended "ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 4 publications
(4 reference statements)
0
13
0
1
Order By: Relevance
“…37,38,40,41 In addition, 2 analytic studies concluded that although they found statistically significant differences between cobedded and separately bedded multiples, the findings were either "not clinically significant" or likely to be "spurious." 36,43 However, these studies were limited by their small sample size and lack of long-term follow-up.…”
Section: Reported Benefits Of Cobedding Multiples In a Hospital Settimentioning
confidence: 96%
See 2 more Smart Citations
“…37,38,40,41 In addition, 2 analytic studies concluded that although they found statistically significant differences between cobedded and separately bedded multiples, the findings were either "not clinically significant" or likely to be "spurious." 36,43 However, these studies were limited by their small sample size and lack of long-term follow-up.…”
Section: Reported Benefits Of Cobedding Multiples In a Hospital Settimentioning
confidence: 96%
“…Of the 5 analytic studies that examined differences in weight gain and growth between cobedded and separately bedded multiples, 36,37,40,41,43,44 2 experimental studies suggested that cobedded multiples may gain weight more readily than separately bedded multiples. 36,44 Researchers who performed a small prospective, randomized study that compared 16 cobedded and 21 separately bedded infants found that cobedded infants had a higher 5-day average daily weight gain.…”
Section: Weight Gain and Growthmentioning
confidence: 98%
See 1 more Smart Citation
“…Baylis et al, for instance, express that current routines in the NICU may foster parental role alteration by moderating an early contact between parents and their child [70]. Several authors indicate that enabling early skinto-skin care for parents [71,72] and the provision of rooming-in [74] or co-bedding [75] contribute to parental role alteration. However, in line with other studies, our findings suggest that routines are not consistent from NICU to NICU [37,73].…”
Section: Discussionmentioning
confidence: 95%
“…Given that the practice of cobedding simulates numerous aspects of environmental and maternal context (proximity, tactile, olfactory, auditory, and memory) that have been shown to provide comfort to newborns, 8,9,[11][12][13][14][15][16][17][18][19] it was reasonable to propose that contact with or the presence of a twin who has shared the same uterine space since conception would have a similar comforting effect. Therefore, we conducted a randomized controlled intervention trial to determine the efficacy of cobedding preterm twins during a tissue breaking procedure (heel lance) in the NICU.…”
mentioning
confidence: 99%